Implementasi Program Nasional Pemberdayaan Masyarakat Mandiri Perkotaan (PNPM-MP) di Desa Gisik Cemandi Kecamatan Sedati Kabupaten Sidoarjo - Yuli Mardani; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2016)
This research aimed to describe and analyze implementation of The National Program of Urban Self Empowerment (PNPM-MP) in the Gisik Cemandi Village, Sedati Sub-District, Sidoarjo Regency; supporting and inhibiting factor in its implementation. This research used qualitative descriptive research. Key informants in this research included member of event organizer in non-governmental organization (PNPM-MP), member non-governmental organization, and head village. The results showed that the implementation of its program was quite good. It is showed that adequate human resources, good coordination between local government, volunteers, and community, characteristics and attitudes implementor enforcement agencies that have a high responsibility to achieve its objectives and realizing the ideals of the poor. Supporting factors in its program implementation namely development and empowerment activities got a positive response from community. Meanwhile, inhibiting factor wasthe lack of discipline for community and community who are less conserve the environment so that the bad habits also remain to be done.